2014
DOI: 10.3357/asem.3673.2014
|View full text |Cite
|
Sign up to set email alerts
|

Electrogastrographic and Autonomic Responses During Oculovestibular Recoupling in Flight Simulation

Abstract: Electrogastrography and interbeat intervals are sensitive indices of autonomic changes in subjects undergoing flight simulation. These data demonstrate the potential of oculovestibular recoupling to stabilize gastric activity and cardiac autonomic changes altered during simulator and motion sickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Multiple authors previously reported on significant changes in GSR due to thermal sweat as a symptom of MS [25,73] as well as changes of other drivers' autonomic responses due to MS, most commonly measured with HR or HR variability (HRV) [22][23][24]. Although not being of primary interest in this study, we explored potential use of those measurements in addition to EGG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple authors previously reported on significant changes in GSR due to thermal sweat as a symptom of MS [25,73] as well as changes of other drivers' autonomic responses due to MS, most commonly measured with HR or HR variability (HRV) [22][23][24]. Although not being of primary interest in this study, we explored potential use of those measurements in addition to EGG.…”
Section: Discussionmentioning
confidence: 99%
“…As subjective measurements could sometimes be biased, there is also an ongoing need in the research community for the development of objective measurement methods [4,5]. Despite low overall success, correlations of drivers' physiological signals with the symptoms of MS have been established through heart rate variability [22][23][24], body temperature [25], skin conductance [25][26][27] and electrogastrogram [27,28]. Among the research, the most often reported and widely studied MS symptom is nausea [4,5,11,25,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Based on pilots' vestibular system restitution pattern follow-Lewkowicz R. et al -The incidence of simulator... Individual diff erences in susceptibility to simulator sickness and its multisymptomatic nature mean that, despite numerous attempts [14,15,19,24,30,61,73,78], no eff ective tool has yet been developed to objectively measure the severity of this sickness. Although there are several measures of simulator sickness that can be used in studies where simulator sickness is expected to be a problem, among the most widely used, wellvalidated measure of simulator sickness is the subjective measurement method involving selfassessment with the Simulator Sickness Questionnaire (SSQ) [7,35,38].…”
Section: Simulator Sickness In a Spatial Disorientation Simulatormentioning
confidence: 99%
“…In recent years, Galvanic Vestibular Stimulation (GVS), the application of low-level electrical current to the vestibular system to induce the sensation of motion, in synchronization with the visual information in flight simulation, has shown potential to provide users with multimodal sensory perceptions and mitigate simulator-induced motion sickness (Cevette et al, 2012 ). This work, building on previous uses of GVS applications (Cevette et al, 2012 , 2014 ), evaluated the ability of GVS to simulate common flight illusions by intentionally providing mismatched GVS applications during flight simulation scenarios in VR. Typically, GVS is achieved by passing current in the range of 1–2.5mA, stimulating the vestibular system, which then interprets the GVS-evoked input like an actual head movement (Fitzpatrick and Day, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pitch and roll perceptions are created with additional electrodes placed on the forehead and nape of the neck electrodes and sending specific patterns of GVS stimulation (Cevette et al, 2010 ). Previously, we integrated GVS with a flight simulation program to synchronize visual and vestibular stimulation in near real-time to demonstrate the potential improved simulator immersion with oculo-vestibular recoupling (OVR; Cevette et al, 2012 , 2014 ). This study investigated whether applying GVS mismatched with the visual scene in a flight simulation environment could be a feasible method to help prepare pilots for the vestibular disturbances that often occur in real flight.…”
Section: Introductionmentioning
confidence: 99%